(untitled) (Journal of Asian Development Studies, 2025)
The present study was conducted to investigate the stressors contributing to occupational burnout among nurses in public hospitals of Multan City, Pakistan. The study highlighted the crucial role of nurses in ensuring the effective functioning of the healthcare system through patient care, emergency management, communication with surgeons, and coordination of care plans. Despite their essential contributions, nurses continue to face numerous socio-cultural and organisational challenges in their work environment, which contribute to their emotional exhaustion. To examine these issues, researchers employed a qualitative research methodology to collect subjective responses based on the real-life experiences of N=17 nurses. An interview guide was formulated to facilitate a comprehensive, contextualised, and in-depth exploration of nurses’ perspectives about the phenomenon. The data were subjected to thematic analysis, resulting in the emergence of subsequent themes: stereotypes associated with the nursing profession, socio-cultural misconceptions about nurses and nursing, work-family conflict experienced by nurses, the dominance of surgeons over nurses, and the contradiction between organisational responsibilities and personal religious principles. In conclusion, the social fabric of public healthcare in Pakistan is founded upon differential stereotypes, anti-religious sentiments, and misogynistic attitudes. This intersection generates various stressors for nurses, including their duty schedules, night shifts, patient care responsibilities, communication with surgeons, and subordinate roles. These stressors have contributed to occupational burnout, prompting some nurses to contemplate resignation. Enhancing public awareness, fostering cultural tolerance, promoting team cohesion, occupational collaboration, and revising hospital policies to safeguard nurses’ rights may alleviate these stressors and mitigate burnout within this structural framework.